Design, simulation and experiment of PSO-FOPID controller for height position control of a scissor mechanism platform - Norsahperi, Nor Mohd Haziq; Ahmad, Salmiah; Toha, Siti Fauziah; Abd Mutalib, Mohd Azri (Faculty of Mechanical Engineering, Belgrade, University of Belgrade, 2022)
This paper proposes the PSO-FOPID controller, which is a Fractional Order Proportional-Integral-Derivative (FOPID) controller tuned using particle swarm optimization with spreading factor algorithm for height position control of a scissor mechanism platform. The tuning process of five control gains in the FOPID controller is technically challenging to achieve high position accuracy. In this study, this problem is addressed through the offline tuning method by using particle swarm optimization with the spreading factor algorithm to reduce the complexity in tuning the control gains. From the experimental study, it is found that the proposed controller can eliminate the steady-state error under the two input references with approximately 1.5% and 0.9% reductions of the overshoot and undershoot in the height position response as compared to its promising performances in simulations. It is envisaged that the PSOFOPID controller can be useful in designing effective height position control of a non-linear platform.